Age, successive waves, immunization, and mortality in elderly COVID-19 hematological patients: EPICOVIDEHA findings - SİLİ, ULUHAN (My University, 2023)
Objectives: Elderly patients with hematologic malignancies face the highest risk of severe COVID-19 outcomes. The infection\"s impact on different age groups remains unstudied in detail. Methods: We analyzed elderly patients (age groups: 65-70, 71-75, 76-80, and >80 years old) with hematologic malignancies included in the EPICOVIDEHA registry between January 2020 and July 2022. Univariable and multivariable Cox regression models were conducted to identify factors influencing death in COVID-19 patients with hematological malignancy. Results: The study included data from 3,603 elderly patients (aged 65 or older) with hematological malignancy, with a majority being male (58.1%) and a significant proportion having comorbidities. The patients were divided into four age groups, and the analysis assessed COVID-19 outcomes, vaccination status, and other variables in relation to age and pandemic waves. The 90-day survival rate for patients with COVID-19 was 71.2%, with significant differences between groups. The pandemic waves had varying impacts, with the first wave affecting patients over 80 years old, the second being more severe in 65-70, and the third being the least severe in all age groups. Factors contributing to 90-day mortality included age, comorbidities, lymphopenia, active malignancy, acute leukemia, less than three vaccine doses, severe COVID-19, and using only corticosteroids as treatment. Conclusion: These data underscore the heterogeneity of elderly hematological patients, highlight the different impacts of COVID-19 waves and the pivotal importance of vaccination, and may help in planning future healthcare efforts.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); İmmünoloji; Mikrobiyoloji; BULAŞICI HASTALIKLAR; MİKROBİYOLOJİ; Life Sciences (LIFE); IMMUNOLOGY; MICROBIOLOGY; INFECTIOUS DISEASES; Mikrobiyoloji (tıbbi); Bulaşıcı hastalıklar; Microbiology (medical); Infectious Diseases; COVID-19; Elderly; Hematological malignancy; High-risk patient; SARS-CoV-2